Understanding the sensory irregularities of esophageal disease. (2nd August 2016) - Farmer, Adam D; Brock, Christina; Frøkjaer, Jens Brøndum; Gregersen, Hans; Khan, Sheeba; Lelic, Dina; Lottrup, Christian; Drewes, Asbjørn Mohr
ABSTRACT: Symptoms relating to esophageal sensory abnormalities can be encountered in the clinical environment. Such sensory abnormalities may be present in demonstrable disease, such as erosive esophagitis, and in the ostensibly normal esophagus, such as non-erosive reflux disease or functional chest pain. In this review, the authors discuss esophageal sensation and the esophageal pain system. In addition, the authors provide a primer concerning the techniques that are available for investigating the autonomic nervous system, neuroimaging and neurophysiology of esophageal sensory function. Such technological advances, whilst not readily available in the clinic may facilitate the stratification and individualization of therapy in disorders of esophageal sensation in the future.